A study on the glycoside content of Euphorbia hirta Linne (Euphorbiaceae) - De Jesus, Ma. Zaida A.; Santos, Rizalina B.; Concepcion. Adoracion B. (Quezon City: Department of Pharmaceutical Chemistry, College of Pharmacy, University of the Philippines, 19983.)
This paper presents an investigation of quercitrin, the glycoside content of Euphorbia hirta Linne. Quercitin was isolated from the aqueous solution of a hydroalcoholic extract of the drug by ether extraction. It was identified by its melting point and its hydrolysis to quercetin. Preliminary tests performed on the aqueous extract of the drug also showed the presence of tannin, plant acids, mucins and proteins, and a small amount of alkaloid. Results of the column chromatography and thin layer chromatography using benzene-acetone (6:4) as eluent to separate the different constituents of the drug are also included in this work.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, November 1983.
Keywords: Euphorbiaceae; Glycosides; Butobutonisan; Gatas-gatas.